Molecular identification of coagulase-negative staphylococci isolated from bovine mastitis and detection of beta-lactam resistance - Srednik, Mariela Elizabeth (2015)
Introduction: Bovine mastitis is a frequent cause of economic loss in dairy herds. Coagulase-negative staphylococci (CoNS) are increasing in importance as cause of bovine intramammary infection throughout the world in recent years. CoNS have been isolated from milk samples collected from cows with clinical and subclinical mastitis in several countries. Identification of mastitis pathogens is important when selecting appropriate antimicrobial therapy. Methodology: A total of 93 strains of Staphylococcus spp isolated from bovine mastitis in Argentina between 2010 and 2013 were identified by PCR-restriction fragment length polymorphism (PCR-RFLP) using the gap gene and were tested for the presence of blaZ and mecA genes by PCR and for the susceptibility to penicillin and cefoxitin by disk diffusion. Results: The most common CoNS species was S. chromogenes 46.2% (43/93), followed by S. devriesei 11.8% (11/93) and S. haemolyticus 9.7% (9/93). The blaZ gene was detected in 19 (20.4%), but only 16 (17.2%) isolates were resistant to penicillin; the mecA was detected in 6 (6.5%) isolates but only 4 (4.3) were resistant to cefoxitin. The 6 mecA-positive isolates showed oxacillin MICs = 0.5 µg/ml. Discussion: CoNS are important minor mastitis pathogens and can be the cause of substantial economic losses. The presence of methicillin resistant isolates emphasizes the importance of identification of CoNS when an intramammary infection is present because of the potential risk of lateral transfer of resistant genes among staphylococcal species.